2021
DOI: 10.1016/j.jsurg.2020.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Education in the Time of COVID: Understanding the Early Response of Surgical Training Programs to the Novel Coronavirus Pandemic

Abstract: Objective Describe the early impact of the COVID-19 pandemic on general surgery residency training nationwide. Design A 31-question electronic survey was distributed to general surgery program directors. Qualitative data underwent iterative coding analysis. Quantitative data were evaluated with summary statistics and bivariate analyses. Participants Eighty-four residency programs (33.6% response rate) with representation across US geographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 12 publications
1
52
0
4
Order By: Relevance
“…All 5 of the orthopaedic training programmes in the United States surveyed by An et al had restructured rotas to include periods of clinical duty followed by remote work and self-isolation [31]. Five studies reported a reduction in trainee presence within the hospital [17,22,23,26,32,33]. Ninety-two percent (60/65) of United States urology programs reported a formal reduction of trainee presence, with a significant decrease in patient-contact time from an average of 4.7 days per week to 2.1 (p < 0.001) [26].…”
Section: Redeployment Non-operative Impact and Change To Working Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 5 of the orthopaedic training programmes in the United States surveyed by An et al had restructured rotas to include periods of clinical duty followed by remote work and self-isolation [31]. Five studies reported a reduction in trainee presence within the hospital [17,22,23,26,32,33]. Ninety-two percent (60/65) of United States urology programs reported a formal reduction of trainee presence, with a significant decrease in patient-contact time from an average of 4.7 days per week to 2.1 (p < 0.001) [26].…”
Section: Redeployment Non-operative Impact and Change To Working Patternsmentioning
confidence: 99%
“…The majority of neurosurgery trainees (139/192) across Italy reported a decrease in the time they spent within the neurosurgical department, part of the strategy to reduce trainee exposure to COVID-19 [22]. A survey of 84 general surgery programme directors in the United States found that all programmes had reduced the number of trainees on daily rounds [33]. In a survey of 504 ophthalmology trainees across 32 countries, 76.4% reported more than a 50% reduction in clinical activity [34].…”
Section: Redeployment Non-operative Impact and Change To Working Patternsmentioning
confidence: 99%
“…This could help confirm and expand initial perceptions and insights that are still being formulated in the research (Feroz et al, 2020;Vindrola-Padros et al, 2021). Previous qualitative studies on COVID-19 and university students have had rather narrow foci, such as evaluating targeted topics with a single country sample (Brondani & Donnelly, 2020;Collado-Boira et al, 2020;Fawaz et al, 2021;Mukhtar et al, 2020;Nguyen et al, 2020;Ramos-Morcillo et al, 2020) or targeted higher educational programs in the health professions (Brondani & Donnelly, 2020;Ramos-Morcillo et al, 2020;White et al, 2020). Further study was needed with a more open approach to broad concerns.…”
mentioning
confidence: 99%
“…While this survey assesses the impact to ophthalmology residents in particular, other surgical specialties have experi-enced similar changes to training volumes and resident wellbeing. 14,19,20 There will continue to be future unavoidable decreases to clinical and surgical volumes due to COVID-19, and it is important for residency training programs to understand the potential impact to this future generation of surgeons and to prepare accordingly. Most importantly, we must prioritize trainee safety by enforcing PPE guidelines and minimizing known COVID-19 exposure as much as possible.…”
Section: Discussionmentioning
confidence: 99%